Comparison of urine Gram stain and urine culture to diagnose urinary tract infection in children - Amalia Utami Putri; Oke Rina; Rosmayanti Rosmayanti; Rafita Ramayati; Rusdidjas Rusdidjas (Indonesian Pediatric Society Publishing House, 2013)
Background Urinary tract infection (UTI) are due to pathogen invasion of the urinary tract. The upper or lower tract may be affected, depending on the presence of infection in the kidney, or bladder and urethra. Infection of urinary tract affect up to 10% of children and are the most common bacterial infection in infants and young children worldwide. The prevalence of UTI is 3-5% in girls and 1 % in boys. Urine culture is considered to be the gold standard diagnostic test for UTI. However, Gram stains of uncentrifuged urine have been done in rural health centers and laboratories in peripheral areas that lack facilities to evaluate urine specimens. Gram stains of urine may be an effective method for ruling out UTI in rural health center patients, thus saving time and money in impoverished settings. Objective To compare urine Gram stain and urine culture as diagnostic tests for UTI in children. Methods This cross-sectional study was held in H. Adam Malik Hospital from May to June 2010. The 54 participants were aged 0 - 14 years, suspected to have UTI and recruited by consecutive sampling. Urine was collected after the external urethral orifice was cleaned. A drop of the urine specimen was Gram stained and examined by a light microscope, while the remainder of the specimen was used for laboratory urine cultures. If Gram negative bacteria were observed by Gram stain, we considered the subject to have UTI. Results The sensitivity and specificity of urine Gram stain compared to urine culture were 88% and 100%, respectively. The positive predictive value (PPV) and negative predictive value (NPV) were 100% and 90%, respectively. Conclusion Urine Gram stain may be a good alternative to urine culture for diagnosing UTI in children living in areas with limited health care facilities.